2021
DOI: 10.9734/jpri/2021/v33i60b34991
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness and Perception on Burning Mouth Syndrome among Dental Students-A Survey

Abstract: Introduction: Burning mouth syndrome is a condition distinguished by painful burning sensation of the tongue and mucosal tissue of the mouth, lips and palate that lasts from a few days to a few months. Common symptoms of burning mouth syndrome include burning sensation in the mouth, altered taste sensation and xerostomia or dry mouth despite normal salivation. Treatment of BMS is by either local or systemic medications that temporarily relieve symptoms and on improving quality of life. Menopausal or postmenopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…The high percentage of PGDSs displaying a low level of UP (80.4%) was also intermediate compared to percentages reported in the literature (Table 4). On one hand, our percentage aligned with findings from some studies 14,16,17,19 (Table 4). For instance, 53% and 69% of 1153 dental students from 62 American and Canadian dental schools believed they should not be responsible for monitoring the academic integrity of other students and did not consider cheating a serious problem at the university.…”
Section: Up Levelsupporting
confidence: 88%
See 4 more Smart Citations
“…The high percentage of PGDSs displaying a low level of UP (80.4%) was also intermediate compared to percentages reported in the literature (Table 4). On one hand, our percentage aligned with findings from some studies 14,16,17,19 (Table 4). For instance, 53% and 69% of 1153 dental students from 62 American and Canadian dental schools believed they should not be responsible for monitoring the academic integrity of other students and did not consider cheating a serious problem at the university.…”
Section: Up Levelsupporting
confidence: 88%
“…In recent years, the phenomenon of plagiarism has emerged as a significant ethical problem, especially among medical students, as evidenced by various studies. 4,[14][15][16][17][18][19][20][25][26][27][28][29][30][31][32] This misconduct in research writing has become widespread worldwide, with high prevalence reported among students from different continents, including America, 29 Europe, 26 Asia, 28,33,34 and Africa. 35,36 Regarding the African continent, Rohwer et al 37 examined biomedical research journal articles and found evidence of plagiarism in 63.2% of the 495 African papers studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations